Analisis Kesulitan Siswa Dalam Menyelesaikan Soal CeritaSistem Persamaan Dan Pertidaksamaan Linier Di Kelas X SMKPrawira Marta Kartasura Tahun Ajaran 2014/2015 - Fatimah, Siti Nur, Rita P. Khotimah, S.Si., M.Sc (2015)
This research aims to analyze the difficulties experienced by students of class X in SMK Butler Marta Kartasura in solving equations and inequalities story linear systems and the factors that cause students difficulty in solving systems of equations and inequalities story linear. This research is descriptive qualitative research. The subjects in this study are students of class X-AP1, amounting to 29 students. Data collection techniques using the test method, observation, interviews, and documentation. The validity of the data by using the triangulation method. The data analysis techniques stage data reduction, data presentation, and conclusion. The results of this study demonstrate the difficulties experienced by students in solving equations and inequalities story linear systems include difficulty understanding the stories question, difficulty changing stories question into mathematical models, difficulty completing mathematical models using elimination and substitution, difficulty completing mathematical models with graphics. The reasons include not understand the concept and have not been able to interpret the sentences presented, have not been able to understand the content of a given problem, not mastered the concept of the use of elimination and substitution, less scrupulous conduct operations algebraic form, has not mastered the concept of creating graphics.